Effect of putative PARG inhibitors identified by an in silico approach on Trypanosoma cruzi infection - Svagzdys, Ailin (2019)
Poly-ADP-ribose polymer signaling is common to various nuclear processes related to DNA metabolism. As a reversible modification, it is regulated by a delicate balance of synthesis and degradation, being poly(ADP-ribose)glycohydrolase (PARG) the major hydrolase. We have demonstrated in mammalian cells that PARG inhibition or silencing is essential for the successful infection by the T. cruzi, making them an interesting target for the search of new treatments for Chagas disease. T. cruzi PARG inhibition also causes a delay in cell cycle. We have compiled a database of molecules tested against human PARG from which, we have inferred 1000 ligand-based classificatory models capable of recognizing hPARG inhibitors using a semicorrelation approach and a random subspace approximation. We have generated a ligand-based model ensemble capable of recognizing human PARG inhibitors, with excellent behavior in the in silico validation step. The ensemble was applied in VS campaign, finding 26 drugs that could potentially behave as PARG inhibitors. Six drugs were chosen based on their solubility and availability and were tested both on infected cells and T. cruzi epimastigote. We analyzed the infection in Vero cells using trypomastigotes expressing β-gal at 96 h PI. At 50 μM, Bromhexine and Rosuvastatine caused a marked reduction on the infection (96% and 55% compared to DMSO infection), while Sulfazalasine and Doxycycline led to a mild reduction in the infection (20% for both drugs). At the indicated concentration, these drugs did not affect host cell growth significantly. When tested on epimastigotes, only Doxycycline demonstrated to affect viability at concentrations ranging from 50-500 μM. These results indicate that while Bromhexine, Rosuvastatine and Sulfazalasine might modulate the infection by affecting the host cell PARG, Doxycycline could possibly be affecting both the parasite and the host cell enzyme, although effects on other molecular targets can not be disregarded.